Sport a tożsamość narodowa. Językowe przejawy budowania wspólnoty obecne w komentarzach sportowych = National identity and sports. The linguistic manifestationsof community building in sports commentary - Grochala, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author describes the linguistic manifestations of community building in TV live sports commentary. She based her research on the football games played by the Polish national team during the Euro 2012 championship, as well as the games of foreign football clubs, in which there are Polish players.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie